Educação ambiental e o uso de agrotóxicos - Fassis, Fabiana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work, we turn our attention to subjects involved in educational activities related to environmental issues in a community where the use of pesticides is present indiscriminately. Thus, our search has taken place towards the construction of possible senses based on the statements of different social characters in this community about the relation between intensive use of pesticides, environmental education and opportunities for political education and empowerment. We seek to discuss examples of society relation - hegemonic nature in contemporary society and the role of education and, more specifically, environmental education processes of the social examples transformations. We assume that education has given priority to human development and therefore assumes its political and emancipatory character building citizenship. The relationship between the educational process and the intensive use of pesticides is chosen as a matter of study and, therefore, we look to explore the main aspects that have been considered by the environmental debate on this issue. The cultural historical approach guided the processes of collection, systematization and analysis of data. The analytical process allowed us to build four cores of meaning, namely: 1) Model of agricultural production and the use of pesticides; 2) Emphasis and appreciation of the knowledge dimension in the educational process; 3) Emphasis on perspectives that point to pedagogical optimism or illusion; 4) Emphasis on the relationship between education and the world of work. From the dialogue between the literature and other researches in the field of environmental education, latent themes related to these core meanings were discussed and investigated as to their meaning for educational processes related to the formation of citizenship

Neste trabalho, voltamos nosso olhar para sujeitos envolvidos com a ação educativa relacionada com a temática ambiental, em uma comunidade onde o uso de agrotóxicos está presente de maneira indiscriminada. Sendo assim, nossa busca se deu em direção à construção de possíveis sentidos a partir dos depoimentos de diferentes atores sociais desta comunidade sobre as relações entre uso intensivo de agrotóxicos, educação ambiental e as possibilidades de formação política e construção da cidadania. Procuramos discutir os modelos de relação sociedade - natureza hegemônicos na sociedade contemporânea e o papel da educação e, mais especificamente, da educação ambiental em processos de transformações desse modelo social. Partimos do pressuposto que a educação tem como prioridade a formação humana e, por isso, assume seu caráter político e emancipatório de construção da cidadania. A relação entre o processo educativo e o uso intensivo dos agrotóxicos é escolhida como questão de estudo e, sendo assim, procuramos explorar os aspectos principais que têm sido considerados pelo debate ambientalista sobre esta questão. A abordagem histórico cultural orientou os processos de coleta, sistematização e análise dos dados. O processo analítico nos permitiu a construção de 4 núcleos de significação, a saber: 1) Modelo de produção agrícola e o uso de agrotóxicos; 2) Ênfase e valorização da dimensão do conhecimento no processo educativo; 3) Ênfase nas perspectivas que apontam para ilusão ou otimismo pedagógico; 4) Ênfase na relação entre educação e o mundo do trabalho. A partir do diálogo com a literatura e com outras pesquisas do campo da educação ambiental os temas latentes relacionados com esses núcleos de sentido foram discutidos e aprofundados quanto aos seus significados para os processos educativos relacionados com a formação da cidadania
Keywords: Environmental education; Educação ambiental; Produtos químicos agrícolas; Educação ambiental - Estudo e ensino